Hubungan Karakteristik Remaja dengan Perilaku Bullying pada Siswa SMP di Kota Padang - Herman, Hermalinda; Nurshal, Deswita; Oktarina, Elvi (Jurusan Keperawatan FIKES UNSOED, 2017)
Bullying is a phenomenon that is common and universal problems in school-age children. Bullying can cause serious/ negative effects concerning the mental health and child welfare. This study aimed to identify the prevalence of bullying in junior high school students in the city of Padang. The study design was descriptive analytic with cross sectional study. Samples are the students of SMP Negeri 31 Padang, SMPN 28 Padang, SMP Muhammadiyah 7 Padang, and SMP Kartika 1-7 Padang with 340 samples. These samples were taken by simple random sampling technique. Data collection tool is questionnaire which consisting of questions on the general data and child bullying behavior questionnaires. Data were analyzed by using Mann Whitney test and Kruskal Wallis. Research shows that almost half of the students’ bullying behavior was verbal bullying, followed by physical bullying and the last was social bullying. There are differentiations regarding bullying behavior by gender and socio-economic. It is expected to develop a research that aimed at the prevention of bullying behavior early on and special interventions which focused on children with low socioeconomic status.